Exploring the History of Islamic Accounting and the Concept of Accountability in an Islamic Perspective - Kautsar Riza Salman (Journal of Islamic Economic and Business Research, 2022)
The history of conventional accounting dominates the literature on the history of accounting, and it is still rare to find a history that describes Islamic accounting comprehensively. In addition, the concept of accountability is still dominated by financial accountability alone. This paper aims to describe the history of Islamic accounting starting from the period of the Prophet until the 20th century. This paper also attempts to describe the concept of accountability from an Islamic perspective. The research approach used in this paper is categorized as qualitative research. The bibliographic method or library analysis used in this study reviews some of the previous literature on the history of Islamic accounting and Islamic accountability. History proves that Muslims have implemented modern and sophisticated accounting systems and practices. The manuscript by Al-Mazindarani entitled "Halakiyah Kitab as-Syiyaqaf Essay" in 765H or 1363M describes the popular accounting practices applied at that time, namely jaridah al-kharaj, jaridah an-nafakat, jaridah al-maal, and jaridah al-masadarin. Even the accounting profession (al-katib) should not be held by everyone and only those who have qualifications such as technical competence, understanding of sharia values, being responsible and trustworthy. The history of Islamic accounting is inseparable from the awareness of avoiding usury, the formation of the first Islamic bank, and the role of professional organizations in terms of regulation of Islamic accounting standards. The Islamic accounting conceptual framework is very different from the conventional accounting conceptual framework in terms of meaning and definition, profit perception, going concern assumption, unit of measurement assumption, and disclosure principle. Accountability in Islam views the responsibility of each individual or company to God as the giver of the mandate (hablum minallah) and to humans (hablum minannas).